Δευτέρα, 30 Αυγούστου 2010

ΧΡΗΣΙΜΕΣ ΤΑΥΤΟΤΗΤΕΣ




Να αποδειχθούν οι ταυτότητες :
• (α+β)^2 = α^2+2αβ+β^2
Απόδειξη: (α+β)^2 = (α+β)(α+β) = α^2+αβ+αβ+β^2=α^2+2αβ+β^2

• (α-β)^2 = α^2-2αβ+β^2
Απόδειξη: (α-β)^2 = (α-β)(α-β) = α^2-αβ-αβ+β^2 = α^2-2αβ+β^2


• α^2-β^2 = (α-β)(α+β)
Απόδειξη: (α-β)(α+β) = α^2+αβ-αβ-β^2 = α^2-β^2

• (α+β)^3 = α^3+3α^2β+3αβ^2+β^3
Απόδειξη: (α+β)^3 = (α+β)(α+β)(α+β) =
= (α^2+αβ+αβ+β^2)(α+β) =
= α^3+2α^2β+αβ^2+α^2β+2αβ^2+β^3
= α^3+3α^2β+3αβ^2+β^3


• (α-β)^3 = α^3-3α^2β+3αβ^2-β^3
Απόδειξη: (α-β)^3 = (α-β)(α-β)(α-β) =
= (α^2-αβ-αβ+β^2)(α-β) =
= α^3-2α^2β+αβ^2-α^2β+2αβ^2-β^3
= α^3-3α^2β+3αβ^2-β^3


• α^3+β^3 = (α+β)(α^2-αβ+β^2)
Απόδειξη: (α+β)(α^2-αβ+β^2) = α^3-α^2β+αβ^2+α^2β-αβ^2+β^3 =
= α^3+β^3


• α^3-β^3 = (α-β)(α^2+αβ+β^2)
Απόδειξη: (α-β)(α^2+αβ+β^2) = α^3+α^2β+αβ^2-α^2β-αβ^2-β^3 =
= α^3-β^3

Αναγνώστες

Αρχειοθήκη ιστολογίου

Univers de particules

Univers de particules
Univers de particules